A case of the higher-level classification of praying mantises (Mantodea) obscuring the synonymy of Majangella Giglio-Tos, 1915 (Liturgusidae, Liturgusinae) and Ephippiomantis Werner, 1922 (Hymenopodidae, Acromantinae) - Svenson, Gavin J.; Vollmer, William (Zootaxa, 2014)
The praying mantis genus Majangella Giglio-Tos, 1915 is taxonomically treated with a re-description of the genus and the two included species, M. moultoni Giglio-Tos, 1915 and M. carli Giglio-Tos, 1915. The genus Ephippiomantis Werner, 1922 is newly determined to be the junior synonym of Majangella Giglio-Tos, 1915 based on morphology. The species for which the genus name Ephippiomantis was erected, E. ophirensis Werner, 1922, is re-described and now included within Majangella. This synonymy was determined herein as the direct result of erroneous higher-level placement of Majangella within the Majanginae by Giglio-Tos and was not recognized even after the genus was moved to within Liturgusidae. Action is now taken to move Majangella from within Liturgusidae to within the Hymenopodidae subfamily of Acromantinae, which is supported by morphological and molecular data. A key to the three species is provided along with habitus images, images of the head, pronotum, and foreleg, and illustrations of the male genitalia. Species distributions are presented and locality coordinates are provided in print as well as being available for download as a KML file viewable in Google Earth.